2017
DOI: 10.9790/1684-1204038794
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation of Flow around External Vehicle: Ahmed Body

Abstract: Abstract:The main objective of this paper is to elucidate a solution to reduce the inefficiencies and losses caused due to major parameters pertaining to the aerodynamics of road vehicle (drag, lift

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 5 publications
1
21
0
7
Order By: Relevance
“…Tujuan utama dari studi ini adalah mengurangi gaya hambatan (drag), meningkatkan penghematan bahan bakar, mencegah gaya angkat (lift) yang tidak diinginkan, dan meminimalkan penyebab ketidakstabilan aerodinamik lainnya pada kecepatan tinggi. Selain itu, memperhitungkan faktor aerodinamis pada desain kendaraan darat untuk mendapatkan kontrol yang baik pada kemudi dan pengereman [1].…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Tujuan utama dari studi ini adalah mengurangi gaya hambatan (drag), meningkatkan penghematan bahan bakar, mencegah gaya angkat (lift) yang tidak diinginkan, dan meminimalkan penyebab ketidakstabilan aerodinamik lainnya pada kecepatan tinggi. Selain itu, memperhitungkan faktor aerodinamis pada desain kendaraan darat untuk mendapatkan kontrol yang baik pada kemudi dan pengereman [1].…”
Section: Pendahuluanunclassified
“…Boundary condition dari pemodelan ahmed body mengikuti penelitian Banga [1] yakni uniform velocity pada inlet dan uniform pressure pada outlet, symmetry pada sumbu ZY. Batas kondisi yang ditetapkan adalah inlet velocity 40 m/s, intensitas turbulen 1% dan rasio viskositas turbulen 10 pada inlet, intensitas turbulen 5% dan rasio viskositas turbulen adalah 10 pada outlet.…”
Section: Boundary Condition and Meshingunclassified
See 1 more Smart Citation
“…The article [3] summarizes the results obtained with different versions of k − realizable model combined with wall functions. The same external air velocity of 40 m s −1 was applied in the study.…”
Section: Introductionmentioning
confidence: 99%
“…The slant on the back side of the body modified the flow physics inside the cavity (Thacker et al, 2013). Banga et al (2015) numerically studied the Ahmed body and found that the velocity vectors in the wake region depend on the slant angle. But the heat transfer due to natural convection on a cavity with Ahmed body is not studied so far.…”
Section: Introductionmentioning
confidence: 99%